Financial Literacy Development Strategy by Using Students’ Engagement Intensification Approach - Pangestika, Mirza Anindya; Yanto, Heri; Rozi, Fahrur (Journal of Economic Education, 2018)
The rapid advance of global economy and the increasing diversity financial product and service types force every individuals to have a good financial literacy in order to achieve prosperous live. The purpose of this study is to identify student engagement contributions as a form of learning process for the development of financial literacy. Academic challenges, active learning, student-staff interaction, enriching education experiences, and supportive learning environments are used to measure student engagement in financial learning (SEFL). While financial knowledge, financial attitudes and financial behavior are used to measure financial literacy (FL). This study uses quantitative assessors. The population is 241 students while the sample size is 150 students. The number of samples is determined by using the Slovin formula, while the sampling technique used is proportional random sampling. The data collection techniques used are tests and questionnaires. While the data analysis techniques used are descriptive analysis, Pearson correlation, canonical correlation and regression. The results of the Pearson correlation analysis show that all SEFL factors possitive correlate with FL factors. Then the results of canonical correlation analysis show that the covariate of SEFL factors has a correlation with the canonical variable (FL). Furthermore, the results of the regression test (t-test) show that most of the SEFL factors have a significant contribution in developing students’ financial literacy.